Sleep homeostasis and cortical synchronization: II. A local field potential study of sleep slow waves in the rat. - Vyazovskiy, V; Riedner, B; Cirelli, C; Tononi, G (2007)
STUDY OBJECTIVE: Sleep slow-wave activity (SWA, EEG power between 0.5 and 4.0 Hz) decreases homeostatically in the course of non-rapid eye movement sleep (NREM) sleep. According to a recent hypothesis, the homeostatic decrease of sleep SWA is due to a progressive decrease in the strength of corticocortical connections. This hypothesis was evaluated in a large-scale thalamocortical model, which showed that a decrease in synaptic strength, implemented through a reduction of postsynaptic currents, resulted in lower sleep SWA in simulated local field potentials (LFP). The decrease in SWA was associated with a decreased proportion of high-amplitude slow waves, a decreased slope of the slow waves, and an increase in the number of multipeak waves. Here we tested the model predictions by obtaining LFP recordings from the rat cerebral cortex and comparing conditions of high homeostatic sleep pressure (early sleep) and low homeostatic sleep pressure (late sleep). DESIGN: Intracortical LFP recordings during baseline sleep and after 6 hours of sleep deprivation. SETTING: Basic sleep research laboratory. PATIENTS OR PARTICIPANTS: WKY adult male rats. INTERVENTIONS: N/A. MEASUREMENTS AND RESULTS: Early sleep (sleep at the beginning of the major sleep phase, sleep immediately after sleep deprivation) was associated with (1) high SWA, (2) many large slow waves, (3) steep slope of slow waves, and (4) rare occurrence of multipeak waves. By contrast, late sleep (sleep at the end of the major sleep phase, sleep several hours after the end of sleep deprivation) was associated with (1) low SWA, (2) few high-amplitude slow waves, (3) reduced slope of slow waves, and (4) more frequent multipeak waves. CONCLUSION: In rats, changes in sleep SWA are associated with changes in the amplitude and slope of slow waves, and in the number of multi-peak waves. Such changes in slow-wave parameters are compatible with the hypothesis that average synaptic strength decreases in the course of sleep.